On Monotone Asymptotic Pointwise Nonexpansive Mappings in Modular Function Spaces. (24th April 2019) - Bin Dehaish, B. A.
Abstract : In this work, we investigate the existence of the fixed points of a monotone asymptotic pointwise nonexpansive mapping defined in a modular function space. Our result extends the fixed point result of Khamsi and Kozlowski.